Sintering Copper Nanoparticles with Photonic Additive for Printed Conductive Patterns by Intense Pulsed Light - Chung, Wan-Yu; Lai, Yi-Chin; Yonezawa, Tetsu; Liao, Ying-Chih (Nanomaterials (Basel, Switzerland), 2019)
In this study, an ink formulation was developed to prepare conductive copper thin films with compact structure by using intense pulsed light (IPL) sintering. To improve inter-particle connections in the sintering process, a cuprous oxide shell was synthesized over copper nanoparticles (CuNP). This cuprous oxide shell can be reduced by IPL with the presence of a reductant and fused to form connection between large copper particles. However, the thermal yield stress after strong IPL sintering resulted in cracks of conductive copper film. Thus, a multiple pulse sintering with an off time of 2 s was needed to reach a low resistivity of 10−5 Ω·cm. To increase the light absorption efficiency and to further decrease voids between CuNPs in the copper film, cupric oxide nanoparticles (CuONP) of 50 nm, were also added into ink. The results showed that these CuONPs can be reduced to copper with a single pulse IPL and fused with the surrounding CuNPs. With an optimal CuNP/CuONP weight ratio of 1/80, the copper film showed a lowest resistivity of 7 × 10−5 Ω·cm, ~25% conductivity of bulk copper, with a single sintering energy at 3.08 J/cm2. The ink can be printed on flexible substrates as conductive tracks and the resistance remained nearly the same after 10,000 bending cycles.